Strategic Steps To Make Effective National Energy Conservation Movement - Myson, Myson (International Journal of Multidisciplinary Sciences and Arts, 2024)
The aim of this research is energy conservation as a pillar of national energy management which has not received adequate attention in Indonesia. The method used in this writing is qualitative descriptive. This method is used to describe the facts in the field. The results achieved in this research are the increasingly popular idea of ??using energy economically as a "smart way of living". The clearest indicator of the work carried out by the energy conservation center and other elements of society is Japan's success in positioning itself as the country with the best energy usage productivity in the world and maintaining this position over the period until now. The conclusion of the results obtained is the acceleration of the formation of an energy saving culture by involving all elements of society with a religious and sociocultural approach.